GRAMMATICAL CHARACTERISTICS OF MODAL WORDS IN ENGLISH. (MEDICINE, PEDAGOGY AND TECHNOLOGY: THEORY AND PRACTICE, 2024)
This article talks about modal words and their important role in linguistics, which have been carefully studied and analyzed by world scientists and linguists of the English language. Since modals are the cause of much discussion and controversy in linguistics, this article analyzes the grammatical and semantic functions of modals.